Performance Study of using Flooding in Industrial Wireless Sensor Networks - BARAĆ, FILIP (My University, 2011)
The applications of Industrial Wireless Sensor Networks (IWSN) for Process Automation(PA) are time-critical and subject to strict requirements in terms of end-to-end delay and reliability of data delivery. A notable shortcoming of the existing wireless industrial communication standards is the existence of overcomplicated routing protocols, whose adequacy for the intended applications is questionable [4]. The aim of this thesis is to evaluate a very well known data dissemination concept of flooding in an industrial setting, to address the viability of exploiting flooding and discover the consequent constraints and benefits for IWSN applications. The vanilla flooding concept is recycled by introducing a number of modifications to define a location-based routing protocol, whose performance is then evaluated in the QualNet simulation environment[2]. The simulation results of all scenarios observed show that this lightweight approach is able to meet stringent performance requirements for networks of considerable sizes. Furthermore, it is shown that this solution significantly outperforms a number of conventional WSN routing protocols in all categories of interest.
Keywords: Informations- och kommunikationsteknik; Datavetenskap (datalogi); Systemteknik; Information & Communication Technology; Computer Science; Systems engineering